2020
DOI: 10.1021/acs.jced.0c00579
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Thiophene, Pyridine, and Toluene from n-Decane as a Diesel Model Using Betaine-Based Natural Deep Eutectic Solvents

Abstract: In an attempt to develop an alternative process that meets the criteria of "green" and economically sound technology in fuel purification, simultaneous extractive desulfurization, denitrification, and dearomatization using natural deep eutectic solvents (NADESs) were investigated. A NADES composed of betaine (Bet) as a hydrogen bond acceptor (HBA) and levulinic acid (LevA) as a hydrogen bond donor (HBD) was investigated for its extraction capacity of thiophene, pyridine, and toluene from n-decane via liquid−li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…The aqueous solutions were prepared as described in Section 2.2. The results in Figure 15 show that the pure component efficiency and the mixture efficiency of the VFAs are almost identical, suggesting that each acid occupies different void sites in the HDES-phase and does not compete with the others under the studied concentrations [36]. It can also be observed that the extraction efficiency was increasing with an increase in VFA chain length as follows: valeric acid (96.5%) > butyric acid (89.9%) > propionic acid (72.3%) > acetic acid (40.5%) with distribution coefficients of 𝛽 13.46, 𝛽 4.36, 𝛽 1.3 , 𝛽 0.36, respectively.…”
Section: Extraction Efficiency Of a Mixture Of Vfamentioning
confidence: 98%
See 1 more Smart Citation
“…The aqueous solutions were prepared as described in Section 2.2. The results in Figure 15 show that the pure component efficiency and the mixture efficiency of the VFAs are almost identical, suggesting that each acid occupies different void sites in the HDES-phase and does not compete with the others under the studied concentrations [36]. It can also be observed that the extraction efficiency was increasing with an increase in VFA chain length as follows: valeric acid (96.5%) > butyric acid (89.9%) > propionic acid (72.3%) > acetic acid (40.5%) with distribution coefficients of 𝛽 13.46, 𝛽 4.36, 𝛽 1.3 , 𝛽 0.36, respectively.…”
Section: Extraction Efficiency Of a Mixture Of Vfamentioning
confidence: 98%
“…The equilibrium cell method [35][36][37] was adopted to measure the solubilities of the pairs: (acetic acid (1) in water or HDES (2)), (propionic acid (1) in water or HDES (2)), (butyric acid (1) in water or HDES (2)), (valeric acid (1) in water or HDES (2)), and the saturation of HDES with water at 298.2 K and 1.01 bar. In this method, 4 g of the mixtures was prepared in 8 mL glass vials.…”
Section: Solubility Testmentioning
confidence: 99%
“…22 Similar studies were performed for NADESs in the extraction of thiophene, pyridine, and toluene from n-decane. 23 The results showed an increase in distribution ratio, selectivity, and extraction efficiency (EE) with the order as follows: pyridine > thiophene > toluene. Rogosǐćand Kucǎn performed the extraction using choline chloride-based DES.…”
Section: Introductionmentioning
confidence: 98%
“…Lemaoui et al studied the simultaneous dearomatization, desulfurization, and denitrogenation of diesel fuels via liquid–liquid extraction . Similar studies were performed for NADESs in the extraction of thiophene, pyridine, and toluene from n -decane . The results showed an increase in distribution ratio, selectivity, and extraction efficiency (EE) with the order as follows: pyridine > thiophene > toluene.…”
Section: Introductionmentioning
confidence: 98%
“…Both DESs have higher selectivity compared to studied ILs and sulfolane as an organic solvent . However, some DESs were used to extract toluene as an aromatic from heptane, n -octane, and n -decane, and the potential of these solvents for extraction of toluene from cyclohexane has not been studied yet. Also, a DES constructed by mixing of tetrabutylphosphonium bromide and levulic acid was utilized for the separation of the cyclic hydrocarbon tetralin from dodecane in an LLE process .…”
Section: Introductionmentioning
confidence: 99%